POSISI HUMAS PEMERINTAH DALAM KRISIS KOMUNIKASI AKIBAT PERUSAKAN KWBT MANDEH - Emeraldy Chatra; Diego Diego; Ilham Havifi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2020)
The issue of damage to the Mandeh tourist area, Pesisir Selatan Regency has gone viral in various print and online media since April 2017. The damage was reported in connection with a project that involved elements of investors, provincial officials and politicians. As a result of the crisis there was a conflict between the regent and the deputy regent. This research questions how the position of PR / Public Relations of the Government in the conflict between the pair of regional heads, environmental communication crisis, tourism and internal communication of the South Pesisir Regency Government. The data were obtained through focus group discussions (FGD), in-depth interviews and field observations. The study found that government public relations did not take any action to overcome the crisis because they were collided by the main duties and functions of the Regent. Public relations also does not face a dilemma because it takes sides with one of the actors in conflict.